Narcissistic parenting in an insecure world : a history of parenting culture 1920s to present / Harry Hendrick. - Hendrick, Harry (Policy Press, 2016)
Harry Hendrick shows how broader social changes, including neoliberalism, feminism, the collapse of the social-democratic ideal and the 'new behaviourism', have led to the rise of the anxious and narcissistic parent, in this provocative history of parenting.